A systematic literature review to assess the burden of herpes zoster disease in China. Issue 2 (1st February 2021) - Yin, Dapeng; Van Oorschot, Desirée; Jiang, Ning; Marijam, Alen; Saha, Debasish; Wu, Zhenhua; Tang, Haiwen; Diaz-Decaro, John; Watson, Phil; Xie, Xueqiong; Ren, Yifan; He, Yu; et al.
ABSTRACT: Introduction: Herpes zoster (HZ) or shingles occurs as a result of reactivation after a primary infection with varicella zoster virus (chickenpox). The burden of HZ in older adults in China is not well understood. We conducted a systematic literature review to understand the burden of disease related to HZ, its complications, and associated costs in China. Areas covered: Using publications retrieved from Chinese and English literature databases, we described incidence and prevalence of HZ, occurrence of HZ-related complications, and costs associated with HZ in mainland China, Taiwan, and Hong Kong. Expert opinion: The data, although limited, indicate that the burden of disease due to HZ is substantial in China, with incidence rates that are comparable to the rest of the world. Recently, an adjuvanted recombinant HZ vaccine was approved for use in China. Disease prevention is likely to reduce the burden of disease, with potentially significant economic benefits. However, understanding the public health impact of vaccination in China will require extensive baseline information about incidence, complication rates, and associated costs. This review gives an overview of available research, but also reveals existing gaps. Well-designed observational studies are needed to quantify the total burden of disease and potential impact of prevention through vaccination. PLAIN LANGUAGE SUMMARY: What is the context? Although Herpes zoster (shingles) is a common disease of older age, the burden of disease in China is not well described. 32% of the Chinese population is aged 50 years and Older and this proportion is increasing. As a result of the ageing population, the public burden associated with shingles is expected to increase over time. What is new? We accessed published studies in the English and Chinese language literature to explore available information describing shingles in China. The incidence of shingles in Taiwan, Hong Kong and mainland China appears to be similar to other countries, although reliable population-based data are currently sparse in Hong Kong and mainland China. What is the impact? Data describing the disease burden due to shingles are currently heterogeneous throughout China. This review is a first step to determine those populations which could benefit most from shingles vaccination. Preventing shingles through vaccination could benefit the individual as well as provide potentially significant economic benefits for the individual, the employer and the economy.